Virtual Internship: Pre-Service Teachers’ Perception - Prasanna, E; Thiyagu, K (Voices of Teachers and Teacher Educators, 2021)
The COVID-19 cases locked different sectors of the world. The education sector also faced a crisis. Acquisition of knowledge should not have an end. Knowledge acquired through internship must be purposeful. It helps to gain experience in one’s preference and is a stepping stone to one who is looking for a job. At present, an essential issue in teacher education is how to design and implement internships. The ongoing COVID-19 lockdown has paved the path for E-internship. The emergency transition to E-internship is by force. E-internship, also known as the virtual internship, is a way of acquiring work experience through a remote setting where the intern is physically absent in an organisation. The study attempts to find the level of perception towards virtual internship because of physical absence. The researcher surveyed participating students, which revealed their general perception, concerns, and technical obstacles regarding virtual internship by responding to the statements provided. The investigator prepared the scale and gave it to them, an analysis of which is given here in this paper. The investigator further analysed the level of pre-service teachers’ perception towards virtual internships. Online learning continues to be a global phenomenon in a variety of fields, but especially in education. The results of this study were; 50 (17.9%) of the sample have low level, 186 (66.4%) of the sample have moderate level, and 44 (15.7%) of the sample have a high level of perception towards virtual internship.